The heterogeneity of cancer stem-like cells at the invasive front. Issue 1 (December 2017) - Yoshida, Go
Abstract Cancer stem-like cells exhibit the multi-functional roles to survive and persist for a long period in the minimal residual disease after the conventional anti-cancer treatments. Cancer stem-like cells of solid malignant tumors which highly express CD44v8-10, the variant isoform of CD44 generated by alternative splicing, has a resistance to redox stress by the robust production of glutathione mediated by ESRP1-CD44v-xCT (cystine/glutamate antiporter) axis. It has been reported that CD44v and c-Myc tend to show the inversed expression pattern at the invasive front of the aggressive tumors. Given that the accumulation of reactive oxygen species triggers the activation of Wnt/β-catenin signal pathway, it is hypothesized that CD44v causes the negative feedback machinery in the regulation of c-Myc expression via the attenuated ROS-induced Wnt signal pathway. To address the fundamental question whether and how both proliferative and quiescent cancer stem-like cells heterogeneously exist at the invasive/metastatic edge, researchers need to investigate into the E3-ubiquitin ligase activity essential for c-Myc degradation. CSCs heterogeneity at the invasive/metastatic front is expected to demonstrate the dynamic tumor evolution with the selective pressure of anti-cancer treatments. Furthermore, the novel molecular targeting therapeutic strategies would be established to disrupt the finely-regulated c-Myc expression in the heterogeneous CSC population in combination with the typical drug-repositioning with xCT inhibitor.